Temporal Variations in Pediatric Trauma: Rationale for Altered Resource Utilization. Issue 6 (June 2018) - Groh, Eric M.; Feingold, Paul L.; Hashimoto, Barry; McDuffie, Lucas A.; Markel, Troy A.
Trauma is a major cause of morbidity and mortality in the pediatric population. However, temporal variations of trauma have not been well characterized and may have implications for appropriate allocation of hospital resources. Data from patients evaluated at an ACS-verified Level I pediatric trauma center between 2011 and 2015 were retrospectively analyzed. Date and time of injury, type of injury (blunt vs penetrating), and postemergency department disposition were reviewed. To assess temporal trends, heatmaps were constructed and a mixed poisson regression model was used to assess statistical significance. Pediatric trauma from blunt and penetrating injuries occurred at significantly higher rates between the hours of 1800 and 0100, on weekends compared with weekdays, and from May to August compared with November to February. These data provide useful information for hospital resource utilization. The emergency department, operating room, and intensive care unit should be prepared for increased trauma-related volume between May and August, weekends, and evening hours by appropriately increasing staff volume and resource availability.